Analisis Pengaruh Faktor Interinsik dan Eksterinsik terhadap Minat Berkunjung Objek Wisata Kota Tua - Rizki Amelia; Adella Patricia (Diploma Travel Business, Faculty of Social and Political Science, Jember University, 2021)
This study aims to analyse the influence of intrinsic and extrinsic factors on the interest of visiting the old city tourist attraction located in the North Jakarta number. By using quantitative descriptive research methods. From 125 respondents, the intrinsically influential interest in visiting the old city is knowledge. While extrinsic factors are strongly influenced by tourism attraction and accessibility of destinations. It is recommended that this research can be continued by using other variables or carried out in other old cities in Indonesia. Keywords: Intrinsic and extrinsic factors, interest in visiting, Tourism Objects, Jakarta Old Town.